Butterflies of the agricultural experiment station of tropical roots and tubers, and Santa Ana, Camagüey, Cuba: an annotated list - Fernández Hernández, Douglas Manuel (Instituto de Ecología, A.C., 2007)
During six years (Nov. 1993 - Nov. 1998, Dec. 2000 - Nov. 2001) monthly occurrence of butterflies, habitats, phenology, adult behaviour, flowers visited, larvae or ovipositions on host plants, and predators were recorded at two sites in Camagüey municipality, Camagüey province, Cuba (The Agricultural Experiment Station of Tropical Roots and Tubers, and Santa Ana), with the purpose of determining the fauna of these localities and discussing aspects of the natural history of each species. Of 111 species recorded only 41 (37%) were permanent residents (18 Hesperiidae, 9 Nymphalidae, 7 Lycaenidae, 6 Pieridae, and 1 Papilionidae). Among the butterflies with insufficient information on distribution was found the skipper Achlyodes munroei, which only occurred as a temporary colonizer, and it had not been collected in Cuba for over half a century. Three of the non-resident species (Junonia evarete, Vanessa cardui and V. atalanta rubria) were new province records. Peaks of abundance and species diversity occurred from June through September in correspondence with the wettest period, however, a small peak also took place in January (the second driest month) when habitats conditions were still favorable and rich seasonal nectar source and larval hosts were available. About 83% (182 species) of the plants present in the localities served as adult or larval resources for butterflies. Acacia farnesiana, Cardiospermum microcarpum and Carica papaya were new host plant records for Ministrymon azia, Cyclargus a. amon and Ascia monuste, respectively.